Enhanced oil recovery from palm oil mill effluent using ultrasonication technique for biodiesel production with two-step esterification and transesterification process - Tang, Yee Mun (2023)

(untitled)
The presence of oil and grease in palm oil mill effluent (POME) showed the possibility to be recovered and valorized as a biodiesel feedstock. However, the complex and relatively resistant impurities in POME limit the full recovery of intracellular lipids. To address this challenge, low frequency ultrasonication was proposed as a pre-treatment to enhance the oil recovery yield by liberating the entrapped oil via the cell disruption technique. This study focused on optimizing the ultrasonication conditions to maximize the improvement of oil recovery yield using Response Surface Methodology (RSM). The optimum conditions of 30.074 % ultrasonication amplitude, 0.167 minutes ultrasonication duration, and 2 cm probe immersion depth resulted in an additional 42.50 % improvement in oil recovery yield over non-treated POME, which is in close agreement with the model’s prediction. Particle size distribution and microscopy analyses on POME demonstrated that ultrasonication was able to induce structural disorganization in the sample. Furthermore, the quality of the oil recovered from POME was not compromised by the intervention of ultrasonication. The costbenefit analysis also revealed that ultrasonication pre-treatment is feasible for improving oil recovery from POME. The study was extended to biodiesel production using POME-recovered oil through two-step esterification and transesterification process. Since these reactions are mass-transfer-restricted processes, the ultrasonication technique was also investigated as a process intensifier to enhance the free fatty acid (FFA) conversion. The ultrasoundintensified techniques outperformed the conventional approach. A maximum FFA conversion of 93 % can be achieved after 1 hour of ultrasonication at 30 % amplitude, with a methanol-to-oil molar ratio of 8:1 and an H2SO4 loading of 0.75 wt%. The attributes of biodiesel produced from POME-recovered oil are comparable to those of palm-based biodiesel in Malaysia. It also satisfies international and local standards, demonstrating its potential as an alternative source for biodiesel production.